Cognitive Profile of Patients With Mitochondrial Chronic Progressive External Ophthalmoplegia - Zhang, Guanyu; Hou, Yue; Wang, Zhaoxia; Ye, Zheng (Frontiers in Neurology, 2020)
Mitochondrial chronic progressive external ophthalmoplegia (CPEO) is a major manifestation of human mitochondrial encephalomyopathies. Previous studies have shown cognitive deficits in patients with mitochondrial diseases. However, these studies often included patients with heterogeneous subtypes of mitochondrial diseases. Here we aimed to provide a better cognitive profile of patients with CPEO by applying a comprehensive battery of neuropsychological assessments in a pure sample of patients with CPEO. We recruited 28 patients with CPEO (19 women, age 16-62 years) and 38 age- and education-matched healthy control subjects (25 women, age 16-60 years). The neuropsychological assessments covered global cognition and five cognitive domains (executive functions, language, working memory, memory, and visuospatial functions). We found that the patients were impaired in global cognition (Montreal Cognitive Assessment), executive functions (Trail Making Test Part B), and language (Boston Naming Test), but not in working memory, memory or visuospatial functions. Moreover, individual patients’ performances in the Trail Making Test Part B (completion time) were predicted by their disease severity (Newcastle Mitochondrial Disease Adult Scale). Namely, the patients with a more severe disease took a longer time to complete the Trail Making Test Part B. No clinical measures predicted individual patients’ performances in the Boston Naming Test.